Dampak Pembelajaran Online Dimasa Pandemi Terhadap Kualitas Tidur Mahasiswa Fakultas Kedokteran Universitas Yarsi Angkatan 2020 - Aditya Kharisma Alviodiva Amanda (Publikasi Indonesia, 2022)
The online learning method is a learning method that utilizes internet network technology that can conduct connectivity and learning interactions through long distances directly without having to meet face to face. Online learning method is a solution used by almost all educational institutions in conducting learning activities during the COVID-19 pandemic. Many studies have been conducted explaining that online learning can disrupt a person's sleep quality. So this study is to find out how the effect of online learning during the pandemic on the quality of sleep of YARSI University Faculty of Medicine students class of 2020. From a population of 207 students of the Faculty of Medicine, YARSI University, Class of 2020, using the slovin formula method, a minimum sample of 137 students was obtained. Data collection is done online using a google form in which there is an inform concern dika indeed the data obtained will be processed into research data. From filling out the questionnaire, data from students was obtained as many as 142 respondents. Then the collected data is processed to find the frequency distribution and find the variable relationship with the spearmans correlation test. Based on the results of the study, the majority of respondents were female (81%) and the average age of respondents was 20 years (74.3%). A total of 119 (83.8%) respondents had poor sleep quality, and the average online learning time carried out by respondents was 5-10 hours per day (77.4%). The results of the spearman rank statistical test obtained a significant number or probability value (0.000) much lower than the significant standard of 0.510 or (p <a). This means that there is a significant relationship between online learning and student sleep quality during the COVID-19 Pandemic.